PELAKSANAAN MGMP DALAM MENINGKATKAN PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM MADRASAH ALIYAH KOTA LANGSA - Fakhrurridha (At- Tarbawi, 2019)
Education has a strategic role in the human resources development. There are many things that have being done to improve the quality of education. Because of that, it needs an expedient to increase the profesionalism of teacher, in this case, one of them is the Islamic religion teacher. Increasing prifesionalism of  Islamic religion teacher is through in-service and on-service training. This reseacrh disscusses on-service training through MGMP in the order to see , doing and evaluating the program of training by MGMP forum. This reseacrh uses kwalitatif approach with descriptive analysis and collecting the data through interview, observation and documentation. The result from this reseacrh shows that MGMP program has made in the early year of teaching and arranged based on guidence book and according to the needs. In the program inserts the activity to increase the profesionalism of teacher like filosofy-threority of Islamic religion teaching, text type (genre base), curriculum systematical and syllabus development, lesson plan arrangment, scientific writing development and classroom action research. Doing once a week and guided by the instructor, use discussion method, answer guestion, problem solving and teaching simulation. The evaluation process was doing by seeing the attendent list, observation, evaluation program and meeting of the teachers that was done by the head of MGMP, prinsipal and supervisor.